2016
DOI: 10.3389/fcvm.2016.00050
|View full text |Cite
|
Sign up to set email alerts
|

The Use of the Ambulatory Arterial Stiffness Index in Patients Suspected of Secondary Hypertension

Abstract: The ambulatory arterial stiffness index (AASI) is a marker of arterial stiffness and is derived from ambulatory 24-h blood pressure registration. We studied whether the AASI could be used as a predictive factor for the presence of renal artery stenosis (RAS) in patients with a suspicion of secondary hypertension and as such as a diagnostic tool for RAS. We included 169 patients with difficult-to-treat hypertension. They all underwent 24-h ambulatory blood pressure monitoring registration, imaging of the renal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…AASI is an easily available marker of arterial stiffness, which can be calculated by the commercially available ABP monitoring devices. AASI has been proven to be associated with cardiovascular adverse events and vascular damage in several clinical settings 14 . The Dublin Outcome Study has shown that AASI is likely to be a more potent predictor of stroke than pulse pressure, particularly in normotensive individuals 15 .…”
Section: Discussionmentioning
confidence: 99%
“…AASI is an easily available marker of arterial stiffness, which can be calculated by the commercially available ABP monitoring devices. AASI has been proven to be associated with cardiovascular adverse events and vascular damage in several clinical settings 14 . The Dublin Outcome Study has shown that AASI is likely to be a more potent predictor of stroke than pulse pressure, particularly in normotensive individuals 15 .…”
Section: Discussionmentioning
confidence: 99%